Spring board and platform diving injuries in elite Chinese divers - Wu, C.; Leung, E.; Li, G.; Zhou, H.; Xu, Z.; Ren, Y. (1999)
From the study of common injuries of 233 platform and spring board divers, 116 divers (69.1%) were found to be injured. The injuries spread over 64 different body parts. The number of chronic injuries was 3 times the number of acute injuries. Technical failures accounted for 67.7% of the injuries. Over-use injuries led to 16.6% of the injuries. 50% of the injuries occurred at water entry. While injured, 43.87% of the divers could continue normal training, about 2% stopped training altogether, and 54.2% could undergo reduced training. Injuries and diseases relating to the cervical spine, retina and vitreous humor of diving athletes have always been under concern, and are regarded as typical injuries of diving. Whilst clinically 6.8% of divers suffered from cervical spine problems and 1% from retinal problems causing visual impairments, which were more than other sports, 2 special researches in respect of pathological diagnosis reveal astonishing results. From six years` observation on 54 national team divers, 50 were found to have different degrees of retinal and vitreous humor diseases. The rate of occurrence and degree of impairment of such diseases were higher in the case of platform divers than springboard divers; more were found among juniors than seniors. It is believed that the hitting of water surface upon entry and the effect of water pressure after entry are directly related, and the repetitive strenuous training on trampoline can also be a source of the problems. At the same time, from the 9-film X-ray cervical spine studies of 112 divers, it was found that 91 (81.2%) divers showed abnormalities. While substantive bony changes or dislocations only comprise 22.9% of the sample, cervical spine abnormalities are related to water impact upon entry. Technical failures leading to cervical spine hyperflexion or extension would cause increased damage.